Second Primary Renal Cell Carcinoma With Nonrenal Malignancies: An Analysis of 118 Cases and a Review of Literature - Chen, Jinchao; Qi, Nienie; Wang, Hua; Wang, Zongping; He, Yedie; Zhu, Shaoxing (Frontiers in Oncology, 2021)
Objectives To evaluate the nature, diagnosis, treatment and prognosis of second primary renal cell carcinoma (SPRCC). Materials and Methods We retrospectively collected data from 118 patients with SPRCC. Clinical characteristics, imaging features and treatments were analyzed and comparisons between SPRCC and renal metastases (RM) were made. Results SPRCC accounts for 11.4% of all RCC. The most common types of extrarenal malignancies included lung, colorectal, breast and gynecological cancers. The median age was 58.5 years old, and 61.0% (72/118) of the patients were male. About 5.1% of the patients presented with symptoms. The average tumor diameter was 4.4 cm (1-8.4 cm). The diagnostic specificity of enhanced computed tomography (CT) was 80.1%. When comparing with RM, more patients with stage I–II extrarenal malignancy and less patients with bilateral, multiple, and endogenic renal masses on computed tomography were found in the SPRCC group. A total of 110 SPRCC patients underwent surgery, including 48 radical nephrectomies and 62 partial nephrectomies. The median overall survival time was 117 months. Female, asymptomatic status, no distant metastasis, and surgical treatment predicted a better survival. Conclusions SPRCC are not uncommon, and it should be considered during the follow-up of patients with nonrenal malignancy. The differential diagnosis between SPRCC and RM was mainly based on imaging and puncture biopsy.